Dividend Policy Determinants of Islamic vs Conventional Companies: is there a Difference? - Khoiruddin, Moh; Alkhomah, Al (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2022)
This study aims to examine the determination of dividend policy in Islamic companies and non-Sharia companies in the manufacturing sector. The dependent variables used are tax, EPS, VOE, institutional ownership, DER, firm size, ROE, MBV, and current ratio with one independent variable namely dividend yield (DY). The population unit used in this study is a manufacturing company listed on the Indonesia Stock Exchange for the 2017-2019 period. Using purposive sampling method to determine the research sample, there are 51 companies consisting of 33 Islamic companies and 18 non-Islamic companies that fall into this category, respectively. Using multiple linear regression as a method of data analysis. The results show that INS, DER, ROE, MBV, CR are significant determinants of dividend policy on Islamic stocks, while INS and CR are significant determinants of dividend policy on non-Islamic stocks in the manufacturing sector. There is a difference in influence between the two.